Mind the gap [age gap problems between employees]. - Schiff, D. (IEEE spectrum)
Although differences between the generations in the workplace are often brushed off as harmless or even humorous, the misunderstandings at times lead to conflict, disgruntlement, and worse. Over time, misunderstandings and miscommunications can accumulate and grow into real rifts. Ultimately, aggrieved professionals may leave their company altogether. Several companies are beginning to recognize the lost productivity and poor morale that stem from generational rifts. Intractable as the problem may appear, say workplace experts, the solution is straightforward: awareness, education, and communication. Generational issues are a subset of communications. If you understand where a person is coming from, it will help you predict their behavior. It will help to know how to communicate with them. This article briefly discusses how to address the problems.